Catalytic consequences of Ga promotion on Cu for CO2 hydrogenation to methanol. Issue 15 (19th July 2017) - Medina, Juan C.; Figueroa, Manuel; Manrique, Raydel; Rodríguez Pereira, Jhonatan; Srinivasan, Priya D.; Bravo-Suárez, Juan J.; Baldovino Medrano, Víctor G.; Jiménez, Romel; Karelovic, Alejandro
Abstract : The addition of Ga to Cu/SiO2 generates new active sites increasing selectivity to methanol. The mechanistic implications are studied by in situ DRIFTS and kinetic experiments. Abstract : The promotion of Ga on SiO2 supported Cu in the hydrogenation of CO2 to methanol at 800 kPa and 200–280 °C was investigated. Cu/SiO2 and CuGa/SiO2 catalysts were prepared by a water-in-oil microemulsion technique resulting in Cu clusters of 4–6.5 nm. It was found that Ga addition increased the methanol formation rate by an order of magnitude without significantly changing that for reverse water gas shift (RWGS). This trend is also evidenced by the decrease in the apparent activation barrier for methanol formation from 78 (for Cu/SiO2 ) to 26–39 kJ mol −1 when Ga was added, but not for RWGS (107–132 kJ mol −1 ). Kinetic and in situ DRIFTS analyses revealed that formate intermediates are adsorbed on both Cu and Ga2 O3 and that methoxy hydrogenation could be the rate determining step of methanol synthesis. In the case of RWGS, a zero order of CO formation with respect to H2 concentration was consistent with a redox mechanism and with the reaction occurring predominantly on Cu sites. The results suggest that Ga promotes Cu increasing methanol selectivity, likely by creating new active sites for methanol formation without modifying its oxidation state, which under reaction conditions remains mostly metallic.